The psychosocial experience and needs of children newly diagnosed with type 1 diabetes from their own perspective: a systematic and narrative review. Issue 10 (12th September 2020) - DeCosta, P.; Grabowski, D.; Skinner, T. C.
Abstract: Aim: To understand the psychosocial experience of children and identify their primary support needs following a type 1 diabetes diagnosis. Methods: A systematic review and narrative synthesis of the literature in this area was conducted. Results: A total of 32 studies were included in the review. At diagnosis, the majority of children experienced high distress, including grief, anxiety, anger, irritation and injection anxiety. The intensity of this reaction decreased rapidly over the following weeks. At diagnosis, rates of depressive symptoms, anxiety, stress disorders and suicidal ideation were elevated. The initial reaction tended to peak shortly after diagnosis and declined over the following year. Thereafter, symptoms of depression and anxiety appeared to increase once again, corresponding with the children's experience of diabetes management and implications as being more difficult and upsetting. Injection anxiety, distress and depressive symptoms persisted for a smaller group of children. Conclusion: The initial high prevalence of depressive symptoms following diagnosis is transitional and should be regarded as a normal adaptive response. To facilitate this adaptive process, specific child‐centred support should be prioritized as an integrated part of early diabetes care. Our findings point to five inter‐related support needs following a type 1 diabetes diagnosis: (1) children need time to adjust to the diagnosis; (2) children need supportive relationships; (3) children need an opportunity for meaningful participation and appropriate protection; (4) children need to engage and explore; and (5) children need to feel supported, but not different. What's new?: A type 1 diabetes diagnosis in childhood represents a time of psychological distress for children and their families. The importance of psychosocial factors in the care and management of type 1 diabetes in childhood is well established, and guidelines on the psychosocial care of children and adolescents with type 1 diabetes are available. This review highlights the need for a child‐centred focus in research and practice and offers a framework to help focus clinical practice and future research. This study proposes five central needs of children recently diagnosed with diabetes; these needs can be used as a starting point for research‐based development of a new practice approach.